2017
DOI: 10.1007/s11259-017-9689-6
|View full text |Cite
|
Sign up to set email alerts
|

Relative abundance of heat shock proteins and clusterin transcripts in spermatozoa collected from boar routinely utilised in an artificial insemination centre: preliminary results

Abstract: It is widely accepted that mature sperm contains RNA. The first hypothesis was that sperm RNAs have no functions of their own but are simply residues of spermatogenesis reflecting the events that occurred during their formation in the testes. More recently new discoveries have essentially expanded these views, showing that sperm mRNAs constitute a population of stable full-length transcripts, many of which are selectively retained during spermatogenesis and delivered to oocytes contributing to early embryo dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Sperm mRNAs can be delivered to the oocyte at fertilization, and correlations between sperm mRNA profiles and embryo cleavage rates suggest that paternally delivered transcripts may affect early zygote development prior to activation of the embryonic genome [22,48,84]. The importance of heat shock proteins in early embryos is well established [47], and previous authors have suggested that the relatively high amounts of hsp70 and hsp90 mRNAs that typify sperm cells might have a role in early embryonic translation (although this has yet to be experimentally investigated) [46]. Moreover, if the downregulation effects we report are representative of a general decay of sperm RNAs, a range of epigenetic factors that influence embryo development could be affected; for example, there is strong experimental evidence that alterations to sperm micro RNAs (miRNAs) caused by the environments experienced by fathers can modify offspring phenotypes [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sperm mRNAs can be delivered to the oocyte at fertilization, and correlations between sperm mRNA profiles and embryo cleavage rates suggest that paternally delivered transcripts may affect early zygote development prior to activation of the embryonic genome [22,48,84]. The importance of heat shock proteins in early embryos is well established [47], and previous authors have suggested that the relatively high amounts of hsp70 and hsp90 mRNAs that typify sperm cells might have a role in early embryonic translation (although this has yet to be experimentally investigated) [46]. Moreover, if the downregulation effects we report are representative of a general decay of sperm RNAs, a range of epigenetic factors that influence embryo development could be affected; for example, there is strong experimental evidence that alterations to sperm micro RNAs (miRNAs) caused by the environments experienced by fathers can modify offspring phenotypes [23].…”
Section: Discussionmentioning
confidence: 99%
“…5-6°C above mean ambient conditions [41,42]. Transcripts from hsp70 and hsp90 are enriched in sperm of disparate taxa, including M. galloprovincialis [27,43], and studies of human and livestock sperm suggest mRNA and protein dynamics of these genes are linked to capacitation and fertility [44][45][46]. Heat shock proteins are also crucial in early embryo development [47], and mRNAs coding for them could be transferred from sperm to fertilized eggs [46,48].…”
Section: Introductionmentioning
confidence: 99%
“…Just like in the case of stallion fertility, a positive correlation between CLU‐positive sperm and spermatozoa abnormalities were observed. Zannoni et al (2017) explored the presence of HSP transcripts, inter alia CLU, in the spermatozoa of boar with proven fertility. The concentration of CLU messenger RNA was very low in comparison with the other studied proteins, for example, the HSP70 and HSP90.…”
Section: Clu Concentration In Seminal Plasmamentioning
confidence: 99%
“…The concentration of CLU messenger RNA was very low in comparison with the other studied proteins, for example, the HSP70 and HSP90. The results of western blot analysis demonstrated the presence of CLU only in the positive control, no signal was observed in the normal spermatozoa samples (Zannoni et al, 2017). Griffiths, Galileo, Aravindan, and Martin‐DeLeon (2009) investigated the role of sCLU as a transporting factor for sperm adhesion molecule 1 (SPAM1) which is considered to be the maturity marker of sperm.…”
Section: Clu Concentration In Seminal Plasmamentioning
confidence: 99%
“…1997). In addition, the HSP70/90 lower expression led sperm quality to low of boar (Zannoni et al 2017). Hsp70 expression may have been upregulated as a protective mechanism against apoptosis in spermatozoa of infertile men (Erata et al 2008).…”
Section: Discussionmentioning
confidence: 97%